PENGARUH INTERVAL PEMBERIAN ZAT PERANGSANG TUMBUH INDOLE BUTYRIC ACID (IBA) TERHADAP PERKECAMBAHAN LONTAR (Borassus Sundaicus Becc) - Jitron Eliaser Tameon; IN Widiartha Mahayasa (Agriculture Faculty of Flores University, 2013)
This research has done in experiment garden of UNDANA , Faculty of agriculture from September 2010 to December 2010. The objective of this research is to find out the interval effect of giving indole butyric acid to the germination of papyrus (Borassus sundaicus Becc). This research used randomized complete experimental (RAL)with five treatments and four re-treatments, a parameter that has been observed involved longer of the root, diameter of the root, time of growth of root, a total of the root, length of root, time of growth of coleoptile and the dry weight of root. The result of this research conclude that the interval effect of giving the growth regulator of indole butyric acid (IBA) to the germination of papyrus in the average of the dry weight of root.where as the others observation variables are the longer average of a pool in the 2nd-week observation, 3rd-week observation, 4th-week observation, 5th-week observation, 6th-week observation and 8th-week observation have significantly effect.effect of treatments as a result of interval different is not unreal in the observation variables of longer of apokol in the 2nd-week observation and 7th-week observation, time of growth of root, total of root and time of growth of coleoptile.